Biofortified crops are sustainably integrated in Nigeria’s food systems and benefiting approximately 13 million consumers - CGIAR Research Program on Agriculture for Nutrition and Health (2021)
A review of the literature, monitoring, evaluation, and impact assessment data to date, and consultations with experts from the public and private sectors revealed that biofortified staples are fully embedded in the Nigerian food system. Biofortification is already benefiting approximately 13 million consumers, with potential to cover the entire country given the most recent developments in integration of biofortified seeds and grain in public policies and programs and increasing private seed and food sector interest and investment in biofortified products.